Chitosan nanoparticle‐mediated delivery of anti‐miR‐203a‐3p for 4T1 triple‐negative breast cancer - Temartenan, Jecklyn Shindy; Fiqri, Hairil; Satriyo, Pamungkas Bagus; Haryana, Sofia Mubarika (Universitas Gadjah Mada, 2026)
Anti‐miR molecules can suppress specific microRNA (miRNA) functions within critical signaling pathways. Chitosan acts as a delivery system for miRNAs; therefore, encapsulating miR‐203a‐3p is essential for targeted delivery and biological activity. This study investigates the impact of chitosan‐encapsulated anti‐miR‐203a‐3p nanoparticles (CS‐NPs) on the viability, proliferation, and migration of triple‐negative breast cancer (TNBC) 4T1 cells. The nanoparticles were synthe‐ sized using the ionic gelation method in a 5:1 ratio of chitosan to anti‐miR‐203a‐3p, incorporating sodium tripolyphosphate (STPP) as a crosslinker. Characterization was conducted using gel electrophoresis and particle size analysis. Cytotoxicity and cell viability were assessed through the MTT assay, while colony formation and wound healing assays evaluated cell proliferation and migration. The nanoparticles demonstrated an encapsulation efficiency of 89.47% and showed significant inhibitory effects on 4T1 cell proliferation and migration. The MTT results indicate an IC50 value of 2.454 µM, while colony formation analysis revealed that both ½ and IC50 doses significantly reduced colony numbers compared to the control. Similarly, wound healing assays showed notable inhibition of cell migration at ¼, ½, and IC50 concentrations. These findings suggest that anti‐miR‐203a‐3p‐loaded CS‐NPs may offer a promising therapeutic approach to managing aggressive breast cancer subtypes, particularly TNBC.